Implementation of the Federal Law «On Protection of Consumer Rights» in the provision of paid medical services: recommendations on signing the contract - M. A. Amkhadova; E. V. Batler; D. G. Ilyuhin; I. A. Petrova (Фармакоэкономика, 2018)
This article addresses the implementation of Federal Law no. 2300-1 dated February 7, 1992 «On the Protection of Consumer Rights» regarding the organization and provision of paid medical assistance. We propose recommendations on properly drafting a contract for the provision of these services. The tasks and challenges of providing the paid medical assistance to the public are analyzed. The adequate timelines, the choice of treatment and the optimal strategies, including those in dental practice, are also discussed.